Efficiency in Northern Ireland hospitals: a non-parametric analysis - McKillop, Donal G.; Glass, J. Colin; Kerr, Christine A.; McCallion, Gillian (Economic & Social Studies, 1999)
The study examines the technical, scale and size efficiency of acute hospitals in Northern Ireland over the six-year period, 1986-1992. The efficiency estimates are used to investigate whether the empirical evidence supports the subsequent current rationalisation policy for hospital provision in Northern Ireland. Non-parametric analysis is used to measure the efficiency of larger and smaller hospitals relative to best practice. The results cautiously support the current policy of expanding larger hospitals and restructuring/closing smaller hospitals, but also indicate that the expansion of large hospitals may not yield substantial efficiency gains.
Keywords: Efficiency; Hospitals; Northern Ireland; Non-parametric analysis; Health services